Hadith #5330 - Sahih al-Bukhari - Rait' bin Khadij (Sahih al-Bukhari)
I said to the Prophet, “We will be facing the enemy tomorrow and we have no knives (for slaughtering)’ He said, “If you slaughter the animal with anything that causes its blood to flow out, and if Allah’s Name is mentioned on slaughtering it, eat of it, unless the killing instrument is a tooth or nail. I will tell you why: As for the tooth, it is a bone; and as for the nail, it is the knife of Ethiopians.” The quick ones among the people got the war booty while the Prophet (ﷺ) was be
Grade: Sahih